Complete Expulsion of Testicular Prosthesis via the Scrotum: A Case-Based Review of the Preventive Surgical Strategies. (2nd June 2015) - Donati-Bourne, Jack; Deb, A.; Jay Mathias, Suresh; Fraser Saxby, Mark; Fernando, Herman
Abstract : Testicular prostheses are regularly used in urological surgery and are important for postoperative psychological well-being in many patients undergoing orchiectomy. One of the recognised complications of this procedure is graft extrusion, which can result in significant morbidity for patients and require operative reintervention. Whilst most cases of extrusion involve upward graft migration to the external inguinal ring or direct displacement through the scrotal skin, we present an unusual case of complete expulsion of testicular implant three weeks postoperatively through a previously healthy scrotum. During surgical insertion of testicular prostheses, the urological surgeon must carefully consider the different surgical strategies at each step of the operation to prevent future extrusion of the graft. A stepwise review of the preventive surgical strategies to reduce the risk of graft extrusion encompasses the choice of optimal surgical incision, the technique of dissection to create the receiving anatomical pouch, the method of fixation of the implant within the receiving hemiscrotum, and the adoption of good postoperative care measures in line with the principles of sound scrotal surgery.